Cross neutralization of Hypnale hypnale (hump-nosed pit viper) venom by polyvalent and monovalent Malayan pit viper antivenoms in vitro and in a rodent model - Tan, Choo Hock; Leong, Poh Kuan; Fung, Shin Yee; Sim, Si Mui; Ponnudurai, Gnanajothy; Ariaratnam, Christeine; Khomvilai, Sumana; Sitprija, Visith; Tan, Nget Hong (Elsevier, 2011)
Hypnale hypnale (hump-nosed pit viper) is a medically important venomous snake in Sri Lanka and Southwestern India. Bite of this snake may result in hemostatic dysfunction, acute kidney injury and death. Clinical studies indicated that the locally available polyvalent antivenoms produced in India are not effective against hump-nosed pit viper envenoming. Hence, there is an urgent need to search for effective antivenom. In this paper, we examined the ability of Calloselasma rhodostoma (Malayan pit viper) monovalent antivenom and the Hemato polyvalent antivenom (both produced by Thai Red Cross Society, TRCS) to neutralize the lethality and toxic effects of H. hypnale venom, as C. rhodostoma is considered a sister taxon of H. hypnale. In vitro neutralization studies showed that the Hemato polyvalent antivenom effectively neutralized the lethality of H. hypnale venom (1.52 mg venom/mL antivenom) as well as the hemorrhagic, procoagulant and necrotic activities of the venom. The monovalent C. rhodostoma antivenom could also neutralize the lethality and toxic activities of the venom, but the potency was lower. The Hemato polyvalent antivenom also effectively protected mice from the lethal and local effects of H. hypnale venom in an in vivo rodent model of envenoming. Furthermore, the polyvalent antivenom could also effectively neutralize the venom of Daboia russelii (2.50 mg venom/mL antivenom), another common cause of snake bites in Sri Lanka and South India. These findings suggested that the Hemato polyvalent antivenom may be beneficial in the antivenom treatment of H. hypnale envenoming.